Special Libraries in the Caribbean: on the Threshold of the New Millennium (Arawak Publications: Jamaica, 2002)
The convergence of information and communications technologies has made a significant impact on the modem information environment. It has created many challenges for library and information professionals in all types of libraries the world over, in both developed and developing countries. Academic, public and school libraries are widely regarded as possessing 'self evident good', and are therefore more likely to obtain the support which will enable them to meet the challenges head on. Special libraries are different however in that these exist to serve the needs of a special sector or group and must continuously justify their existence to survive particularly in harsh economic climates. Sharing information and strategies for coping and providing quality service is certainly one way of strengthening the options available to special librarians. It is for this reason that Special Libraries in the Caribbean on the Threshold of the new Millennium - a conference sponsored jointly by the Commonwealth Library Association (COMLA) and the Jamaica Library Association (JLA) is regarded as timely and important.
Keywords: Special Libraries -- Caribbean Area